Some pyrazole derivatives as corrosion inhibitors for carbon steel in hydrochloric acid solutions - Motawea, Mohamed Sobhi; Abdelaziz, Mahmoud Ali (European Journal of Chemistry, 2015)
Two pyrazole derivatives, namely 2,4-diamino-5-(5-amino-3-hydroxy-1H-pyrazole-1-carbonyl)thiophene-3-carbonitrile (I) and 1-(2,4-diamino-5-(5-amino-3-hydroxy-1H-pyrazole-1-carbonyl)thiophen-3-yl)propan-1-one (II) were evaluated as a corrosion inhibitors for carbon steel in 1M hydrochloric acid by weight loss, potentiodynamic polarization and electrochemical impedance spectroscopy methods. Spectrophotometric and conductometric titration methods were also utilized to investigate the possibilities of chemical adsorption between the steel surface and the compounds under consideration. The results showed that the studied compounds inhibit the corrosion of steel in acidic solution at different temperatures. The adsorption followed the Langmuir isotherm. The thermodynamic and the activation parameters were also determined and discussed.